P167 Sexual dysfunction and associated factors in young patients with Crohn's disease. (27th May 2021) - Rodríguez, A; Herreros, B; Muñoz, R; Sempere, L; Bernal, L; Hurtado, A; Orts, B; Zapater, P; Moreno, O; Gutiérrez, A
Abstract: Background: The prevalence of sexual dysfunction (SD) in general population has been estimated up to 30% in women and 5% in men, and 50% and 25% in IBD patients, respectively. We aimed to compare the rates of SD in young patients with Crohn's disease (CD) with healthy controls (HC), as well as to identify SD associated factors in CD patients. Methods: This was a cross-sectional, case-control, observational study, including CD out-patients, aged 18–40 years-old, and HC paired by gender and age. Sociodemographic and disease features were recorded. SD was measured by the Index of Female Sexual Function(IFSF) in women, and by International Index of Erectile Function(IIFE-15) in men. Psychological functioning was evaluated using the Hospital Anxiety and Depression Scale [HAD], and quality of life in IBD by SIBDQ-9. Differences between groups were statistically compared. Results: A total of 122 subjects were included:73 men(48 CD, 25 HC) and 49 women(21 CD, 28 HC). Nineteen percent of CD women and 8.3% of men had active disease according to Harvey-Bradshaw Index. Nineteen percent of CD women and 6.3% of men were receiving steroids, 23.8% and 14.6% immunosuppressants, and 71.4% and 72.9% biologics, respectively. CD women had more sedentary lifestyle than HC(38.1% vs 3.6%, p=0.005). In women SD rates were 35% in CD vs 12% in HC(p < 0.08). Mean IFSF values were lower in CD women(27 CD vs 30 HC, p=0.02), as well as in the desire item(3.5 CD vs 4.3 HC, p=0.005). SD in men did not show significant difference between groups. Mean IIFE values differed between CD and HC(53.6 vs 67.2, p=0.001), as well as erectile disfunction, orgasm and global satisfaction(p< 0.05)(Table 1). Main factors associated with an abnormal SD in CD women were high fecal calprotectine, current use of steroids, lower SIBDQ score and higher depression score(p<0.05). Although disease features or current treatments did not correlate to SD in CD men, both perianal disease and surgery were associated with lower values of orgasm domain (p<0.05). Conclusion: In our serie SD was numerically higher in CD patients compared to HS. SD in CD women, but not in men, was driven by disease activity, current steroid treatment and depression.